Quinoline-based HIV Integrase Inhibitors - Musiol, Robert (Current Pharmaceutical Design, 2013)
HIV integrase became an important target for drug development more than twenty years ago. However, progress has been hampered by the lack of assays suitable for high throughput screening, a reliable crystal structure or pharmacophore. Thus, a real breakthrough was only observed in 2007 with the introduction of the first integrase inhibitor, raltegravir, into treatment. To date, the armament of integrase inhibitors is broad and covers several drugs from different classes that are under clinical trials. Among them, quinoline-based compounds and analogues occupy an important place. This review is focused on those compounds that have a quinoline scaffold and attempts to answer the question of whether quinoline is privileged for these activities. In fact, quinoline has been claimed as a privileged structure several times for different fields of activities. A closer look at its structural features may reveal the prerequisites responsible for the popularity of quinoline-based inhibitors of HIV integrase.
Keywords: HIV integrase inhibitors